A population-based prospective study on obesity-related non-communicable diseases in northern Iran: rationale, study design, and baseline analysis - Motamed, Nima; Zamani, Farhad; Maadi, Mansooreh; Ajdarkosh, Hossein; Roozafzai, Farzin; Keyvani, Hossein; Poustchi, Hossein; Shakeri, Ramin; Ashrafi, G. Hossein; Perumal, Dhayaneethie; Rabiee, Behnam; Moradi-Lakeh, Maziar; et al. (Frontiers in Endocrinology, 2024)
Background Iran is facing an epidemiological transition with the increasing burden of noncommunicable diseases, such as obesity-related disorders and cardiovascular diseases (CVDs). We conducted a population-based prospective study to assess the prevalence and incidence rates of CVDs and obesity-related metabolic disorders and to evaluate the predictive ability of various CVD risk assessment tools in an Iranian population. Methods We enrolled 5,799 participants in Amol, a city in northern Iran, in 2009-2010 and carried out the first repeated measurement (RM) after seven years (2016)(2017). For all participants, demographic, anthropometric, laboratory, hepatobiliary imaging, and electrocardiography data have been collected in the enrollment and the RM. After enrollment, all participants have been and will be followed up annually for 20 years, both actively and passively. Results We adopted a multidisciplinary approach to overcome barriers to participation and achieved a 7-year follow-up success rate of 93.0% with an active follow-up of 5,394 participants aged 18-90 years. In the RM, about 64.0% of men and 81.2% of women were obese or overweight. In 2017, about 16.2% and 5.2% of men had moderate or severe non-alcoholic fatty liver disease, while women had a significantly higher prevalence of metabolic syndrome (35.9%), and type 2 diabetes mellitus (20.9%) than men. Of 160 deceased participants, 69 cases (43.1%) died due to CVDs over seven years.The most prevalent obesity-related chronic disease in the study was metabolic syndrome. Across the enrollment and RM phases, women exhibited a higher prevalence of obesityrelated metabolic disorders. Focusing on obesity-related metabolic disorders in a population not represented previously and a multidisciplinary approach for enrolling and following up were the strengths of this study. The study outcomes offer an evidence base for future research and inform policies regarding non-communicable diseases in northern Iran.